Differences in the Tensor Veli Palatini Between Adults With and Without Cleft Palate Using High-Resolution 3-Dimensional Magnetic Resonance Imaging. (May 2018) - George, Thomas N.; Kotlarek, Katelyn J.; Kuehn, David P.; Sutton, Bradley P.; Perry, Jamie L.
Objective: To investigate the dimensions of the tensor veli palatini (TVP) muscle in adults with and without cleft palate. Design: Prospective study. Participants: There were a total of 14 adult participants, 8 noncleft and 6 with cleft palate. Methods: Analysis and comparison of the TVP muscle and surrounding structures was completed using 3D MRI data and Amira 5.5 Visualization Modeling software. TVP muscle volume, hamular process distance, mucosal thickness, TVP muscle length, and TVP muscle diameter were used for comparison between participant groups based upon previous research methods. Results: Mann-Whitney U tests revealed a significantly smaller ( U < .001, P = .002) TVP muscle volume in the cleft palate group (median = 536.22 mm 3 ) compared to individuals in the non–cleft palate group (median = 895.19 mm 3 ). The TVP muscle was also significantly shorter ( U = 1.00, P = .003) in the cleft palate group (median = 18.04 mm) versus the non–cleft palate (median = 21.18 mm). No significant differences were noted for the other measured parameters. Conclusion: Significant differences in the TVP muscle volume and length among the noncleft participants found in this study may insights into the reported increased incidence of otitis media with effusion (OME) seen in the cleft population. Results from this study contribute to our understanding of the underlying anatomic differences among individuals with cleft palate.